2006
DOI: 10.1016/j.carres.2006.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Iterative one-pot syntheses of chitotetroses

Abstract: Rapid syntheses of chitotetrose derivatives were achieved in good yields using the newly developed reactivity independent iterative one-pot strategy. The protective groups on donors and acceptors were independently evaluated allowing matching of the two partners in glycosylation. No anomeric reactivity adjustments or intermediate purification were necessary thus significantly improving the overall synthetic efficiency. Only near stoichiometric amounts of building blocks were required for the assembly of target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 49 publications
(9 reference statements)
0
43
0
Order By: Relevance
“…[29] This is particularly advantageous for syntheses of oligosaccharides, which consist of repeating units, as the same building blocks can be used repeatedly without resorting to anomeric reactivity adjustments. [28,29] Herein, we explore the applicability of the iterative one-pot method in construction of the highly challenging sHA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[29] This is particularly advantageous for syntheses of oligosaccharides, which consist of repeating units, as the same building blocks can be used repeatedly without resorting to anomeric reactivity adjustments. [28,29] Herein, we explore the applicability of the iterative one-pot method in construction of the highly challenging sHA.…”
Section: Resultsmentioning
confidence: 99%
“…[28,29] Moreover, unlike the traditional reactivity based one-pot approach where glycosylation reactions must be performed in the order of decreasing donor anomeric reactivity values, [30,31] it is not necessary to fine-tune anomeric reactivities using the pre-activation method. [29] This is particularly advantageous for syntheses of oligosaccharides, which consist of repeating units, as the same building blocks can be used repeatedly without resorting to anomeric reactivity adjustments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple glycosylations can be performed in a single reaction flask without intermediate oligosaccharide purifications, thus significantly expediting the glycoassembly process. We have demonstrated that this is a powerful methodology, which has been successfully applied in syntheses of linear oligosaccharides, including hyaluronic acid oligosaccharides, 14 heparin trisaccharides, 15 chitotetraose, 16 and GloboH. 17 Herein, we report the application of the pre-activation based methodology to one-pot construction of branched oligosaccharides.…”
mentioning
confidence: 99%